2015
DOI: 10.1186/s13071-015-1131-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the strategy to eliminate human African trypanosomiasis in the Democratic Republic of Congo

Abstract: BackgroundThe virulent vector-borne disease, Gambian human African trypanosomiasis (HAT), is one of several diseases targeted for elimination by the World Health Organization. This article utilises human case data from a high-endemicity region of the Democratic Republic of Congo in conjunction with a suite of novel mechanistic mathematical models to address the effectiveness of on-going active screening and treatment programmes and compute the likely time to elimination as a public health problem (i.e. <1 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
187
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(189 citation statements)
references
References 35 publications
2
187
0
Order By: Relevance
“…The simple and fast nature of this method indicates it could be suitable for the high-throughput processing of tsetse. With prevalence of T. b. gambiense in tsetse from HAT foci predicted to be as low as 1 in 10 5 (17), there is a need for a xenomonitoring tool which can be applied to large numbers of samples. With further optimisation of the assay and DNA extraction protocol, our method could be applied in the remote and low-resource settings typical of most HAT cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple and fast nature of this method indicates it could be suitable for the high-throughput processing of tsetse. With prevalence of T. b. gambiense in tsetse from HAT foci predicted to be as low as 1 in 10 5 (17), there is a need for a xenomonitoring tool which can be applied to large numbers of samples. With further optimisation of the assay and DNA extraction protocol, our method could be applied in the remote and low-resource settings typical of most HAT cases.…”
Section: Discussionmentioning
confidence: 99%
“…This study was also challenged by the unavailability of any field-caught T. b. gambiense infected tsetse flies. As previously mentioned, trypanosome prevalence in HAT foci is predicted to be very low (17), therefore making obtaining sufficient field samples for assay validation an ongoing challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to tsetse population dynamics described above, adult tsetse in each cell progress through susceptible teneral (juvenile unfed) ( S V ) to either susceptible non-teneral ( G V ), or exposed ( E 1V – E 3V ) and then infectious ( I V ) classes. Instead of having a fixed-time for the tsetse incubation period, or assuming that the incubation period is exponentially distributed, we model three exposed classes as per [14], assuming an Erlang distributed waiting time for the extrinsic incubation period [15]. Hosts in each cell progress through susceptible ( S H ), exposed ( E H ), infected/ infectious ( I H ) and recovered ( R H ) classes.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioural studies have shown that this species is responsive to Tiny Targets [13]. Accordingly, we implemented a large-scale trial of Tiny Targets in Yasa Bonga Health Zone, one of the foci where the addition of vector control to screening activities is predicted to accelerate progress towards the elimination goal [4,6]. To assist in the design and monitoring of the tsetse control operation, we also conducted a large-scale entomological survey of G. f. quanzensis in Yasa Bonga and its neighbouring health zones of Masi Manimba and Mosango ( Figure 1) and used remotely-sensed data to produce a map of tsetse habitat suitability for this important vector, which guided the deployment of targets and allowed us to assess their impact.…”
Section: Introductionmentioning
confidence: 99%